1991
DOI: 10.21236/ada241291
|View full text |Cite
|
Sign up to set email alerts
|

The Impossibility of Implementing Reliable communication in the Face of Crashes

Abstract: Unclassified-2a. SECURITY CLASSIFICATION AUTHORITY 3. DISTRIBUTION /AVAILABILITY OF REPORT Approved for public release; distribution 2b. OECLASSIFICATION/DO)WNGRADING SCHEDULE is unlimited. 4. PERFORMING ORGANIZATION REPORT NUMBER(S) 5. MONITORING ORGANIZATION REPORT NUMBER(S) Massachusetts Institute of Technology N00014-85-KY0168/NO0014-91-J-iU46 N00014-83-K-0125/NO0014-8 9 J-i 98 8 6a. NAME OF PERFORMING ORGANIZATION 6b. OFFICE SYMBOL 7a. NAME-OF MONITORING ORGANIZATION MIT Lab for Computer Science (if appic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Building on earlier work by Fekete, Lynch, Mansour, and Spinelli [131], they showed that an algorithm in this model can be driven into a global state that contains any combination of reachable local states. It follows easily that problems such as leader election and mutual exclusion are impossible in this model.…”
Section: Other Problemsmentioning
confidence: 95%
See 1 more Smart Citation
“…Building on earlier work by Fekete, Lynch, Mansour, and Spinelli [131], they showed that an algorithm in this model can be driven into a global state that contains any combination of reachable local states. It follows easily that problems such as leader election and mutual exclusion are impossible in this model.…”
Section: Other Problemsmentioning
confidence: 95%
“…Fekete and Lynch [130] proved that there are no headerless protocols that tolerate packet losses, so the alternating bit protocol uses the shortest possible headers. When the sender and the receiver can fail by losing the information stored in their local memories, Fekete, Lynch, Mansour and Spinelli [131] proved that no protocol can tolerate packet losses, even for an easier version of the problem where the sequence of messages can be output by the receiver in any order. For more general networks where packet losses can occur, Adler and Fich [5] proved lower bounds on the size of packet headers necessary for sequence transmission when intermediate nodes do not store information.…”
Section: Fault Modelsmentioning
confidence: 99%
“…A number of impossibility results consider distributed consensus in general (see [13][14][15]). In [22], the author shows that the presence of communication failures makes impossible to deterministically reach consensus (Theorem 5.1) and any r-round algorithm has probability of disagreement of at least 1 r+1 (Theorem 5.5).…”
Section: Related Workmentioning
confidence: 99%
“…Without statistical multiplexing, the actual state of a communication task is theoretically not confirmable [22,14,42]. With statistical multiplexing, the probability of success increases proportionally as the number of redundant computing and communication paths.…”
Section: Motivationsmentioning
confidence: 99%